Upaya Pendidikan Sufistik dalam Pengembangan Psikologi Modern - Zainal Badri, Khairul Nizam bin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2020)
This article seeks to examine the efforts of sufi education and their relation to the field of psychology, especially from a positive developmental perspective. This is because modern psychology tends to study human development, which is negative, while the scope of research in positive human development is worth paying attention to. Although modern psychology recognizes humanity as the central center of life, the fact is that the field is more focused on mental symptoms, rather than exploring the inner potential of humanity. In this regard, Sufis education can serve as an alternative ground, which can be used in modern psychology. This is because Sufis education in the context of psychology has methods that can expand the inner potential of man.